2018
DOI: 10.14740/cr732w
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width and Mortality in Patients With Acute Coronary Syndrome: A Meta-Analysis on Prognosis

Abstract: BackgroundRed cell distribution width (RDW), a routine component of the complete blood count (CBC), measures variation in the size of circulating erythrocytes. It has been associated with several clinical outcomes in cardiovascular disease. We sought to strengthen the association between RDW and mortality in patients admitted for acute coronary syndrome (ACS) by pooling together data from available studies.MethodsStudies that fulfilled the following were identified for analysis: 1) observational; 2) included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 32 publications
(26 reference statements)
4
36
1
1
Order By: Relevance
“…The inflammatory state and oxidative stress change the morphology, deforming force, and half-life of red blood cells, increase RDW in vivo, and cause changes in hemodynamic state [27]. RDW clinically influences the severity and prognosis of stroke, acute coronary syndrome, and other diseases [28,29]. Our study displays that preoperative RDW is associated with cognitive decline in CHD patients undergoing CABG.…”
Section: Discussionmentioning
confidence: 74%
“…The inflammatory state and oxidative stress change the morphology, deforming force, and half-life of red blood cells, increase RDW in vivo, and cause changes in hemodynamic state [27]. RDW clinically influences the severity and prognosis of stroke, acute coronary syndrome, and other diseases [28,29]. Our study displays that preoperative RDW is associated with cognitive decline in CHD patients undergoing CABG.…”
Section: Discussionmentioning
confidence: 74%
“…Elevated RDW level is also known as anisocytosis. Several studies in recent years have shown that RDW can be used as a potent predictor of morbidity and mortality in a variety of settings, particularly in many cardiovascular problems, such as coronary heart disease, pulmonary arterial hypertension, and HF . The role of RDW in HF is unclear, but its value in HF has been demonstrated to be independent of anemia .…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell distribution width (RDW) is a parameter of the haemogram used in the differential diagnosis of anaemia and involves the variability in form and size of red blood cells in the subject [17] . An association between high RDW and mortality has been found in patients with coronary disease [18] , liver disease [19] , pancreatitis [20] and ischemic stroke [21] , [22] . This association has also been found in septic patients [23] , [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%